Analysis of Students' English Reading Comprehension through KWL (Know-Want-Learn) Learning Strategies - Eva Yuni Rahmawati (International Journal of Language Teaching and Education, 2018)
This research aims to know the reading comprehension of students through KWL learning strategies. The research is descriptive research survey. The subject of research is the student of Mathematics Education Program who learned English. A sample of this research used sampling Simple Random Sampling (n = 40). Data collection is done by carrying out a test of reading using the test, after the students being treated by KWL learning strategies. Analysis of research data using descriptive statistical techniques. The results showed that on the item reserved text reading comprehension there is 75% of the students who were able to resolve the matter at this stage determine the topic, 62.5% of the students were only able to resolve the matter at this stage determine the word citation and 67.5% of students were able to determine at the conclusion of the recitation and 50% specify detail information. It can be concluded that the KWL strategy is able to improve students reading comprehension. Key Words: Know-Want-Learn Learning Strategies, Reading Comprehension, English.